∫ 0 π / 2 sin 2 t ⋅ ln ( sin t ) d t
The value of the integral above can be expressed as b π a ( c − ln d ) , where a , b , c , and d are integers.
Find the smallest possible value of a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
β ( x , y ) = 2 ∫ 0 2 π sin 2 x − 1 ( t ) cos 2 y − 1 ( t ) d t d x d β ( x , y ) = 2 d x d ∫ 0 2 π sin 2 x − 1 ( t ) cos 2 y − 1 ( t ) d t β ( x , y ) ( ψ ( x ) − ψ ( x + y ) ) = 4 ∫ 0 2 π sin 2 x − 1 ( t ) cos 2 y − 1 ( t ) ln ( sin ( t ) ) d t β ( 2 3 , 2 1 ) ( ψ ( 2 3 ) − ψ ( 2 ) ) = 4 ∫ 0 2 π sin 2 ( t ) ln ( sin ( t ) ) d t 2 π ( ( 2 − 2 ln ( 2 ) − γ ) − ( 1 − γ ) ) = 4 I I = 8 π ( 1 − 2 ln ( 2 ) ) = 8 π ( 1 − ln ( 4 ) ) a = 1 , b = 8 , c = 1 , d = 4 Note: β ( 2 3 , 2 1 ) = Γ ( 2 3 + 2 1 ) Γ ( 2 3 ) Γ ( 2 1 ) = Γ ( 2 ) 2 1 Γ ( 2 1 ) Γ ( 2 1 ) = 2 π / / Γ ( 2 1 ) = π / / Γ ( n + 1 ) = n Γ ( n ) ψ ( 2 3 ) = ψ ( 1 + 2 1 ) = 2 − γ − 2 ln ( 2 ) / / ψ ( n + 2 1 ) = − γ − 2 ln ( 2 ) − k = 1 ∑ n 2 k − 1 1 = ψ ( 2 ) = 1 + ψ ( 1 ) / / ψ ( n + 1 ) = n 1 + ψ ( n ) / / ψ ( 1 ) = − γ d x d B ( x , y ) = B ( x , y ) ( ψ ( x ) − ψ ( x + y ) ) x = 2 3 , y = 2 1 β ( 2 3 , 2 1 ) = 2 π , ψ ( 2 3 ) = 2 − 2 ln ( 2 ) − γ , ψ ( 2 ) = 1 − γ
∫ sin 2 ( t ) lo g ( sin ( t ) ) d t ⇒ 8 1 ( 2 i Li 2 ( e 2 i t ) + 2 t ( i t − 2 lo g ( 1 − e 2 i t ) + 2 lo g ( sin ( t ) ) + 1 ) + sin ( 2 t ) ( 1 − 2 lo g ( sin ( t ) ) ) )
8 1 ( 2 i Li 2 ( e 2 i t ) + 2 t ( i t − 2 lo g ( 1 − e 2 i t ) + 2 lo g ( sin ( t ) ) + 1 ) + sin ( 2 t ) ( 1 − 2 lo g ( sin ( t ) ) ) ) ⇒ ( 8 1 ( π ( 1 + 2 i π − 2 lo g ( 2 ) ) − 6 1 ( i π 2 ) ) ) − ( 2 4 i π 2 ) ⇒ 8 1 π 1 ( 1 − lo g ( 4 ) )
Problem Loading...
Note Loading...
Set Loading...
I = ∫ 0 2 π sin 2 t ln ( sin t ) d t = ∫ 0 2 π 2 1 ( 1 − cos 2 t ) ln ( sin t ) d t = 2 1 ( t − 2 sin 2 t ) ln ( sin t ) ∣ ∣ ∣ ∣ 0 2 π − 2 1 ∫ 0 2 π t cot t d t + 4 1 ∫ 0 2 π sin 2 t cot t d t = 0 − 2 1 t ln ( sin t ) ∣ ∣ ∣ ∣ 0 2 π + 2 1 ∫ 0 2 π ln ( sin t ) d t + 2 1 ∫ 0 2 π cos 2 t d t = 0 − 0 − 4 π ln 2 + 4 1 ∫ 0 2 π ( 1 + cos 2 t ) d t = − 4 π ln 2 + 4 1 [ t + 2 sin 2 t ] 0 2 π = − 4 π ln 2 + 8 π = 8 π ( 1 − ln 4 ) Using integration by parts By integration by parts again See note: ∫ 0 2 π ln ( sin x ) d x = − 2 π ln 2
Therefore, a + b + c + d = 1 + 8 + 1 + 4 = 1 4 .
Note:
J = ∫ 0 2 π ln ( sin x ) d x = 2 1 ∫ 0 2 π ( ln ( sin x ) + ln ( cos x ) ) d x = 2 1 ∫ 0 2 π ln ( sin x cos x ) d x = 2 1 ∫ 0 2 π ln ( 2 sin 2 x ) d x = 2 1 ∫ 0 2 π ln ( sin 2 x ) d x − 2 1 ∫ 0 2 π ln 2 d x = 4 1 ∫ 0 π ln ( sin u ) d u − 4 π ln 2 = 2 1 ∫ 0 2 π ln ( sin u ) d u − 4 π ln 2 = 2 1 J − 4 π ln 2 = − 2 π ln 2 By identity: ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x Let u = 2 x ⟹ d u = 2 d x Since ln ( sin u ) is symmetrical about u = 2 π Note that ∫ 0 2 π ln ( sin u ) d u = J